Analysis of Nutritional Status of Adolescent Girls: Challenges, Interventions, and Health Implication (Literature Review) - Rukmaini; Suraini; Vivi Silawati (International Journal of Midwifery and Health Sciences, 2024)
This study aims to analyze the nutritional status of adolescent girls, focusing on the prevalence of anemia, malnutrition, and obesity, as well as the factors influencing them. Data used were derived from previous research conducted in various regions of Indonesia, including West Java and Depok, as well as a literature review from sources such as the 2021 Basic Health Research (Riskesdas). Additionally, this study examines the effectiveness of nutritional education interventions in improving adolescent knowledge and attitudes toward nutrition and anemia prevention. The results indicate that the prevalence of anemia among adolescent girls reaches 27.3% nationally and 30% in West Java. Nutritional education delivered through social media and interactive methods such as PAKEM (Active, Creative, Effective, and Fun Learning) has proven effective in increasing knowledge. These findings emphasize the importance of educational interventions and increased physical activity to address nutritional issues among adolescent girls.